A Multi-Agent Distributed Data Mining Model Based on Algorithm Analysis and Task Prediction - Dan Zhou; Wenbi Rao; Fangsu Lv (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
This paper accentuates an approach of implementing Distributed Data Mining using Multi-Agent technology and proposes a Multi-Agent Distributed Data Mining model. Each Agent is only responsible for specific duties. Agents communicate and coordinate with each other, which enhances the privacy and confidentiality of data. An Algorithm Analysis Agent is presented to improve the intelligence and efficiency of Data Mining Agent in the model. To improve the performance of communication between Agents and reduce the pressure of network bandwidth, Load Balancing Agent and Task Prediction Agent are put forward. It also makes the performance comparison with the traditional Distributed Data Mining model.